Diabetic Muscle Infarction: A Rare Complication of Long-Standing and Poorly Controlled Diabetes Mellitus - Shridhar N. Iyer; Almond J. Drake; R. Lee West; Robert J. Tanenberg (Case Reports in Medicine)
Objective. To report a case of diabetic muscle infarction (DMI), a rare complication of long-standing poorly controlled diabetes mellitus. Methods. We describe a case of a 45-year-old male with an approximately 8-year history of poorly controlled type 2 diabetes mellitus with multiple microvascular complications who presented with the sudden onset of left thigh pain and swelling. He had a swollen left thigh and a CK of 1670 U/L. He was initially treated with intravenous antibiotics for a presumptive diagnosis of pyomyositis or necrotizing fasciitis with no improvement. A diagnosis of diabetic muscle infarction was considered. Results. An MRI of the thigh demonstrated diffuse edema in the anterior compartment. A muscle biopsy demonstrated coagulation necrosis in skeletal muscle and inflammation and infarction in the walls of small blood vessels. These studies confirmed the final diagnosis of DMI. He was treated with supportive care and gradually improved. Conclusion. DMI is a rare complication of diabetes that is often mistaken for infections such as pyomyositis and necrotizing fasciitis or thrombophlebitis. Treatment is supportive. Although the short-term prognosis is good in these patients, the long-term prognosis is poor.